2006
DOI: 10.2164/jandrol.05134
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Torsion Alters the Presence of Specific Proteins in the Mouse Testis as Well as the Phosphorylation Status of Specific Proteins

Abstract: Testicular torsion followed by torsion repair induces an ischemia-reperfusion injury to the testis that can render the testis aspermatogenic. Previous results have demonstrated this loss of spermatogenesis to be the result of germ cell apoptosis induced by oxidative stress. The present work reports protein changes occurring in the mouse testis 24 hours after repair of a testicular torsion known to induce germ cell apoptosis and severe seminiferous impairment. Total proteins were extracted from sham-operated te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
4
8
0
Order By: Relevance
“…the decline in the testicular membrane constituents, protein and phospholipid, content in the present study lend support to this contention. The cholesterol content, however, was raised, perhaps due to the accumulation in the face of reported decline in testicular androgen production suggesting I/R stress might play a role in Leydig cell dysfunction, as well as by acting directly in germ cell apoptosis [23]. Similar observations have been reported in the literature in higher period of torsion earlier.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…the decline in the testicular membrane constituents, protein and phospholipid, content in the present study lend support to this contention. The cholesterol content, however, was raised, perhaps due to the accumulation in the face of reported decline in testicular androgen production suggesting I/R stress might play a role in Leydig cell dysfunction, as well as by acting directly in germ cell apoptosis [23]. Similar observations have been reported in the literature in higher period of torsion earlier.…”
Section: Discussionsupporting
confidence: 84%
“…The formation of multinucleated cells, constituted by young spermatids have been shown in another study [22], similar observations in rats using D-thio-glucose were reported earlier [23]. This is a compound that interferes with glucose metabolism [24].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These two pro-inflammatory factors are secreted from reperfusing leukocytes, including neutrophils [18] and hematogenous macrophages, which infiltrate into the interstitial spaces surrounding damaged tubules [23][24][25]. Nevertheless, other testicular cells, including Sertoli and Leydig cells, do not undergo apoptosis after I/R injury, although I/R-affected Leydig cells transiently cease steroid hormone secretion [2,32]. Several studies have reported expression and activation of pro-apoptotic signal molecules in experimental testicular I/R [14,19], but the role of intracellular signaling in the survival of testicular cells after I/R is poorly understood.…”
mentioning
confidence: 99%
“…The Akt/protein kinase B (PKB) and extracellular signal-regulated kinase (ERK) 1/2 pathways mediate various growth factor-stimulated processes, such as cell division, growth, differentiation, and survival, in testicular cells [10,13,16,21,31,32]. Akt/PKB and ERK1/2 signaling, the most thoroughly investigated survival signals thus far, are involved in in vitro and/or in vivo cell survival after I/R injury in the brain [27], kidney [15,29], and heart [11,22].…”
mentioning
confidence: 99%